Analysing the mechanisms of failure in polycarbonate sheets deformed by SPIF - A. Rosa-Sainz; J.P. Magrinho; M.F. Vaz; M.B. Silva; G. Centeno; C. Vallellano (Journal of Materials Research and Technology, 2024)
This article presents experimental research conducted on polycarbonate sheets deformed via single-point incremental forming (SPIF). Building upon established frameworks from previous studies, the analysis focuses on evaluating the formability and failure modes, particularly necking and fracture, of polymeric sheets in both conventional and incremental forming processes. The experimental design encompasses an investigation of spindle speed and step down process parameters, utilizing both oil and water as lubricants, to comprehensively assess their effects. The findings provide insights into how these parameters influence formability and affect the failure mode. When using oil as a lubricant, three distinct failure modes were observed during deformation: fracture, twisting, and crazing. An increased twisting was associated with higher step down values, whereas elevated spindle speeds contributed to increase crazing. Additionally, these tests revealed a “post-crazing” failure mode following deformation. Conversely, when water was used as a lubricant, only fracture and twisting were observed in the SPIF specimens. This work introduces, for the first time ever, a complete investigation of these failure modes through scanning electron microscopy analysis of the failure surface. This analysis scrutinizes surface features and interprets them, thus providing a valuable tool for failure analysis.